Posttraumatic Stress and Distress Tolerance: Associations With Suicidality in Acute-Care Psychiatric Inpatients. Issue 7 (July 2017) - Vujanovic, Anka A.; Bakhshaie, Jafar; Martin, Colleen; Reddy, Madhavi K.; Anestis, Michael D.
Abstract : Abstract: Trauma and posttraumatic stress disorder (PTSD) symptomatology have been associated with suicidality, including ideation and behavior. The current investigation evaluated, in acute-care psychiatric inpatients, the mediating role of perceived (self-reported) distress tolerance in the association between PTSD symptom severity and suicidality, defined as a) suicidal ideation, intent, or behavior leading to current psychiatric hospitalization; b) self-reported severity of suicidal desire; and c) percentage of days of suicidality during current hospitalization. Participants were composed of 105 adults (55.2% women; mean age, 33.9; SD, 10.9) admitted to a public psychiatric acute-care inpatient hospital in a large metropolitan area; 52.3% of the participants were hospitalized for suicidality. Results indicated that PTSD symptom severity (and severity of each PTSD symptom cluster) may exert an indirect effect on suicidality, specifically suicidality as a basis for current hospital admission and self-reported severity of suicidal desire, through perceived distress tolerance. Effects were documented after controlling for theoretically relevant covariates.